Echocardiographic recovery changes in patients supported with veno-arterial extracorporeal membrane oxygenator and weaning success. (14th October 2021) - Gonzalez Martin, J; Alonso-Fernandez-Gatta, M; Merchan Gomez, S; Gonzalez Cebrian, M; Diego-Nieto, A; Martin-Herrero, F; Toranzo-Nieto, I; Barrio-Rodriguez, A; Rodriguez-Estevez, L; Sanchez-Fernandez, P L
Abstract: Introduction: The weaning from veno-arterial extracorporeal membrane oxygenation (VA-ECMO) decision involves a meticulous evaluation of different factors, among which echocardiography is a decisive factor. Purpose: Evaluate echocardiographic changes from the beginning of the support to the weaning test. Methods: Analysis of VA-ECMO cases in a referral hospital which completed a weaning test. We evaluated the changes of echocardiographic parameters during the VA-ECMO support (initial and during weaning test) and successful weaning (survival >24h after explant and no mortality from cardiogenic shock/heart failure or cardiac arrest during admission). Results: 85 out of 134 VA-ECMO patients were included from 2013 to Oct-2020 (table 1.1). Successful weaning was achieved in 61.2% and final survival at discharge 49.4%. We observed a significant increase in left ventricular ejection fraction (LVEF), left ventricular outflow tract time–velocity integral (LVOT VTI), tricuspid annular plane systolic excursion (TAPSE) and the percentage of patients with normal qualitative right ventricular function and 1:1 aortic valve opening from the initial to the weaning echocardiography (table 1.2), without significant changes in ventricular diameters. Among these changes, the increase in LVOT VTI was the only parameter that was related to weaning success (p=0.037, table 1.2). A higher LVEF increase from the initial value showed a trend to greater successful VA-ECMO disconnection (p=0.053 table 1.2). Conclusion: Left and right ventricular function parameters improved significantly from baseline to weaning test echocardiography in VA-ECMO supported patients. Of these changes, the increase in LVOT VTI was related to successful disconnection from VA-ECMO and the LVEF improvement showed a trend to weaning success. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Instituto de Salud Carlos III in Spain (Co-funded by European Social Fund "Investing in your future").